REVOLUSI DIGITAL DALAM STUDI HADIS: TAKHRIJ MATAN DAN RIJAL MELALUI JAWAMI’ AL-KALIM - Lainuvar (AL-ATSAR: Jurnal Ilmu Hadits, 2025)
This research article presents a structured, comprehensive, and detailed explanation of the features available in the Jawami' al-Kalim software and how it can be used for the takhrīj (verification and referencing) of both rijāl (narrators) and matn (text) of hadith. In addition, for more in-depth information, this article also includes a preliminary explanation of the concepts of takhrij of matn and rijal. The method used in this research is library research in which the author collects data from relevant literature such as books, journal articles, notes, and other supporting documents. The results showed that Jawami' al-Kalim software is exceptionally comprehensive. It offers a wide range of features to support takhrīj needs, including tools for al-jarḥ wa al-ta‘dīl (narrator evaluation), matn authentication, and access to primary hadith sources and reference works essential for hadith researchers. The author also provides a complete description of the and step-by-step guidance for performing takhrīj of narrators and hadith texts. The article also concludes that takhrīj of matn and rijāl is no longer limited to traditional manual methods using classical texts, but can now be effectively done digitally using software—among which Jawāmi‘ al-Kalim stands out as one of the most complete software solutions for hadith verification. Keywords: Hadith Studies, Digital Revolution, Jawami' al-Kalim, Takhrīj al-Matn, Takhrīj al-Rijāl.